PENGARUH AKTIVITAS DAN MOTIVASI BELAJAR TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 7 MAKASSAR - Pulukadang, Saina; ., Muzakkir; Ibrahim, Misykat Malik (Universitas Islam Negeri Alauddin Makassar, 2018)
The effect of activity and learning motivation on the formation of the religious character of students in Makassar 7 Public High School is intended to increase the learning activeness and learning motivation of students in the subjects of Islamic Education to form the relativistic character of students. This type of research is ex post facto using a quantitative approach. The population amounted to 944, a sample of 94 students, using the Proportionate Stratified Random Sampling technique. The research instruments were questionnaires, documentation, and observation. The data obtained were analyzed using descriptive and inferential statistics, namely simple and multiple linear regression analysis techniques. The results of this study gave the conclusion that the learning activities of students influence the formation of the religious character of students. This can be seen from the results of the analysis, namely the value of the calculated t variable X1 is greater than the value of the t table (10,233> 2,364) with a significant level below 0.05 which is 0,000. The results of the analysis of the value of the calculated t variable X2 are greater than the value of the t table (21,776> 2,364) with a significant level below 0.05 which is 0,000. Significant F value of 0,000 (<0.05), the hypothesis is accepted